The collaborative peer-feedback for the continuous improvement of products - Cesareni, Donatella; Sansone, Nadia (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2019)
The contribution describes a peer-feedback activity in a university course, during which students build knowledge products and are called to improve them through mutual feedback. The course lasted 10 weeks divided into 3 modules; 109 students in 11 groups participated. The study aims to track the evolution of students’ critical skills. To this end, we analyzed: a pre-post questionnaire for self-assessment of critical skills (N = 90), the peer-feedback sheets produced by the work groups (N = 44). The results of the questionnaire show statistically significant differences in all the itemsinvestigated. As for the peer feedback, the analysis shows a significant improvement in the quality of the comments provided. Overall, the articulation of the activities seems to support the development of skills aimed at developing and improving collaborative knowledge products.